Development of Analytical Models for RC Columns under Blast loading Considering Strain Rate Effects - Esmaeilnia Omran, Mohammad; Mollaei, Somayeh (International Journal of Integrated Engineering, 2017)
One of the most important examples of transverse excitation of beam-columns is structural reinforced concrete (RC) columns under blast loading. Under accidental or intentional explosions next to the buildings, external columns are the most critical and vulnerable structural elements. In this paper, tow analytical approaches are used to predict the first maximum dynamic response of rectangular RC column under simultaneously effect of axial force and transverse blast loading. The first analytical model is based on continuous formulation of Euler-Bernoulli beam theory and the second model is a single degree of freedom (SDOF) approach. Both of the approaches consider strain rate effects on nonlinear behavior of materials (concrete and steel reinforcement) and secondary effects of P-Î´. Results of proposed models for predicting the first maximum lateral response of column under impulsive, dynamic and quasi-static loading regimes are compared to the results of nonlinear finite element analysis. The outcomes indicate undesirable discrepancies under high levels of axial force and quasi-static loading conditions. Nevertheless, in the impulsive and dynamic regimesÂ and moderate and low axial load ratio, the differences in the results are acceptable. Afterward, the analytical models are used to evaluate Pressure-Impulse (P-I) diagram for RC column under blast loading and effective factors on it.